2018
DOI: 10.1051/matecconf/201821004019
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Machine Learning Algorithms and Diversity in Data

Abstract: Recent world events in go games between human and artificial intelligence called AlphaGo showed the big advancement in machine learning technologies. While AlphaGo was trained using real world data, AlphaGo Zero was trained using massive random data, and the fact that AlphaGo Zero won AlphaGo completely revealed that diversity and size in training data is important for better performance for the machine learning algorithms, especially in deep learning algorithms of neural networks. On the other hand, artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The predictive and prescriptive power of the algorithms depended partly on the training datasets, and may have restricted algorithms in making early-season crop management decisions. Algorithms capture information present in the data, and the limited variation among the attributes in the training datasets may have affected the performance of the algorithms in the beginning of the experimental period [65]. However, the idea of the experiment was that over the course of the season, the AI algorithms would be improved on the basis of provided management decisions and their effects on greenhouse climate and crop production.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive and prescriptive power of the algorithms depended partly on the training datasets, and may have restricted algorithms in making early-season crop management decisions. Algorithms capture information present in the data, and the limited variation among the attributes in the training datasets may have affected the performance of the algorithms in the beginning of the experimental period [65]. However, the idea of the experiment was that over the course of the season, the AI algorithms would be improved on the basis of provided management decisions and their effects on greenhouse climate and crop production.…”
Section: Discussionmentioning
confidence: 99%
“…However, what constitutes a reasonable data size is uncertain and context-dependent. Typically, decision trees, naïve Bayes and support vector machine algorithms tend to perform better on small and medium-sized datasets, while random forests, k-nearest neighbors, and artificial neural networks may perform better on larger datasets [ 38 , 39 ]. Similar studies in the literature have been observed to use datasets of different sizes.…”
Section: Datasetmentioning
confidence: 99%
“…8 For effective training of machine learning models used in UAV detection, the environment in which the UAVs operate should provide variation in landscape, weather conditions, time of day, and terrain features. 9 Additionally, machine learning models require specific dataset formats for training. 10 Output data should follow conventional ML formats, including label and bounding box information of all aerial objects rendered.…”
Section: Introductionmentioning
confidence: 99%